Broad geographical distribution and high genetic diversity of shrew-borne Seewis hantavirus in Central Europe - Schlegel, Mathias; Radosa, Lukáš; Rosenfeld, Ulrike M; Schmidt, Sabrina; Triebenbacher, Cornelia; Löhr, Paul-Walter; Fuchs, Dieter; Heroldová, Marta; Jánová, Eva; Stanko, Michal; Mošanský, Ladislav; Fričová, Jana; et al. (Virus genes, 2012)
For a long time hantaviruses were believed to be exclusively rodent-borne pathogens. Recent findings of numerous shrew- and mole-borne hantaviruses raise important questions on their phylogenetic origin. The objective of our study was to prove the presence and distribution of shrew-associated Seewis virus (SWSV) in different Sorex species in Central Europe. Therefore, a total of 353 Sorex araneus, 59 S. minutus, 27 S. coronatus, and one S. alpinus were collected in Germany, the Czech Republic, and Slovakia. Screening by hantavirus-specific L-segment RT-PCR revealed specific amplification products in tissues of 49 out of 353 S. araneus and four out of 59 S. minutus. S-segment sequences were obtained for 45 of the L-segment positive S. araneus and all four L-segment positive S. minutus. Phylogenetic investigation of these sequences from Germany, the Czech Republic, and Slovakia demonstrated their similarity to SWSV sequences from Hungary, Finland, Austria, and other sites in Germany. The low intra-cluster sequence variability and the high inter-cluster divergence suggest a long-term SWSV evolution in isolated Sorex populations. In 28 of the 49 SWSV S-segment sequences, an additional putative open reading frame (ORF) on the opposite strand to the nucleocapsid protein-encoding ORF was identified. This is the first comprehensive sequence analysis of SWSV strains from Germany, the Czech Republic, and Slovakia, indicating its broad geographical distribution and high genetic divergence. Future studies have to prove whether both S. araneus and S. minutus represent SWSV reservoir hosts or spillover infections are responsible for the parallel molecular detection of SWSV in both species.
Keywords: zvířata; Genetic Variation; Animals; RNA virová; rejskovití; Česká republika; Německo; Reverse Transcriptase Polymerase Chain Reaction; Czech Republic; fylogeneze; Orthohantavirus; Germany; polymerázová řetězová reakce s reverzní transkripcí; Sequence Analysis, DNA; sekvenční analýza DNA; Hantavirus; Hantavirus Infections; Slovakia; Slovenská republika; Phylogeny; hantavirové infekce; Shrews; genetická variace; RNA, Viral